Efficacy and Adverse Events of PD-1 Inhibitors in Patients With Advanced Urothelial Carcinoma From a Real-World Experience - Sun, Fengze; Wang, Dawei; Liu, Aina; Wang, Tianqi; Zhang, Dongxu; Yao, Huibao; Sun, Kai; Zhou, Zhongbao; Lu, Guoliang; Wu, Jitao (Frontiers in Pharmacology, 2022)
bstract Background: Programmed death 1 (PD-1) inhibitors—tislelizumab, toripalimab, camrelizumab, and sintilimab—are used for advanced urothelial carcinoma (UC) in China. To date, the efficacy and adverse events (AEs) of these PD-1 inhibitors have been poorly reported for advanced UC. Methods: We reviewed 118 patients treated with PD-1 inhibitors for advanced UC from July 2019 to October 2021 at Yantai Yuhuangding Hospital. Patient data were obtained from hospital records and telephone follow-ups. The safety and efficacy of PD-1 inhibitors were assessed by RESIST and Common Terminology Criteria for Adverse Events (version 4.0), respectively. Results: During a median follow-up period of 6 months, 112 patients (95%) experienced AEs; of these, 104 (88%) were grade 1-2 AEs, and 60 (51%) were grade 3-4 AEs. The most common AE was anemia, and no patients died as a result of treatment. A sub-analysis according to treatment method (PD-1 inhibitor vs. PD-1 inhibitor plus chemotherapy) was performed. The incidence of grade 1-2 AEs was not different between the groups (85% vs. 94%), but combination therapy significantly increased grade 3-4 AEs (32% vs. 89%). Monotherapy and combination therapy also did not differ with regard to immune-related AEs of grade 1-2 (13% vs. 22%) or grade 3-4 (1% vs. 6%). In efficacy, complete response was not observed, but 33 patients (28%) had partial response, 30 (25%) had stable disease, and 47 had progressive disease (40%). The overall response and disease control rates were 28% and 53%, respectively. Preliminary efficacy of disease control was better with combination therapy versus monotherapy (78% vs. 43%). Conclusion: PD-1 inhibitors show promising tolerance and efficacy in advanced UC. PD-1 inhibitors combined with chemotherapy offered better disease control but had more grade 3-4 AEs. The clinical use of combination therapy warrants caution.